Survey In The Economy: Crisis And Economic Policy - Cabrera, César (1977)
In 1975 the country appeared at the first signs of an economic crisis that, over time, has shown a progressive worsening. This crisis is just one more in the economic history of the country that seems to be marked by the periodic presentation of consecutive crises, whose "inevitability" suggests the existence of focus located in the very heart of the economic system that affects its functionality.